Coping strategies of Ghanaian couples after unsuccessful infertility treatment: An exploratory qualitative study - Stephen Mensah Arhin; Kwesi Boadu Mensah; Isaac Tabiri Henneh; Felix Yirdong; Evans Kofi Agbeno; Charles Ansah; Martins Ekor (PLoS ONE, 2025)
Background Psychological distress and social burdens associated with infertility among couples have been well-documented. However, little is known about the specific coping strategies employed by couples in low-middle-income countries such as Ghana, in the aftermath of unsuccessful infertility treatment attempts. In this qualitative study, we explored specific coping strategies patients adopt to address psychological distress related to unsuccessful treatment for infertility. Methods A semi-structured interview approach was used to elicit qualitative responses from 18 fertility clients after unsuccessful treatment at four fertility clinics in Ghana. Thematic analysis (TA) was used to examine the coping strategies adopted by participants in response to psychological distress associated with infertility treatment failures. This allowed us to explore potential culturally specific coping strategies employed by participants in response to infertility-related psychological distress. Results The themes that emerged as coping strategies in response to infertility-related psychological distress were diversional activities, intrapersonal cognitive reframing, social isolation, familial support, religious coping, avoidance-focused coping strategies, seeking encouragement, and professional help. Conclusion The findings from this study indicate that coping strategies that involve isolating oneself may not provide lasting emotional relief for individuals experiencing infertility. Relational activities contribute positively to coping. This is relevant in helping health professionals in the management of infertility treatment failures, which may include setting up support groups of similar experiences to draw strength from each. Furthermore, the results underscore the need to integrate psychological interventions into the counseling of couples following an unsuccessful infertility treatment. The clinical and research implications of these findings are discussed.